Beyond time and space: case study of three Chinese translations of The Screwtape Letters by C.S. Lewis from cross-cultural translingual perspectives - Liu, Xuejing (Nanyang Technological University, 2023)
The history of translation is closely related to religious materials. Yet the translation of religious materials pose some of the greatest challenges. While significant amount of translation studies have been done for the translation of religious scripts such as The Holy Bible and Buddhist cannons, religious literary translation might have been understudied. Accurate translation of literary works is vital not only for people of particular faith, but also serves as outreach channels for outsiders to know more about that faith, that in turn promotes harmony. The author of this paper aims to establish a systematic approach to analyse the translation of religious literature from cross-cultural perspectives, and chooses Christian literature as its case study. By proposing CIPP (Cultural Distance/Awareness, Ideology, Poetics, Patronage) model and analysing three successful Chinese translations of The Screwtape Letters from different eras and regions under the CIPP model, this paper seeks to shed light on how such considerations contribute to the cross-cultural translation of Christian literature and provide guidance for translators. With soaring demand for Christian literature across Mainland China, Hong Kong, Taiwan and other overseas Chinese communities, the study of Chinese Christian literature is both timely and important, especially for Singapore for its strategic geographic location and position amidst major Chinese regions and overseas Chinese communities. The author also proposes extended CIPP model for literature works of other religions and non-religious literature, hoping that all three CIPP models could help translators to be more aware of the cultural context and difference that arise from the change of time and space, so as to translate the source text for the target text readers appropriately, sensitively and adequately. In a multi-ethnic, multi-cultural and multi-religions society such as Singapore, the study of cross-cultural translations for religious and non-religious literary work are meaningful for both academic studies and social advocacies to promote racial harmony.